Estratégia didática para o ensino de química utilizando os alimentos orgânicos como enfoque - Vivian, Medianeira Gueller (2024)
The research emerged from a professional observation, which verified the interest of students in the theme "organic foods". From the application of a diagnostic evaluation, in which the discourse was that organic foods "have no chemistry" or "have little chemistry", it was realized the need to demystify the chemistry present in foods from organic production. The question that guides this research is: What is the relevance of a didactic sequence contextualized with the theme of "organic foods" to demystify the presence of chemical elements in the composition of these foods? The general objective is to develop, apply and evaluate a didactic sequence supported by the Three Pedagogical Moments, addressing the theme of organic foods in the teaching of Chemistry in the first year of high school. The didactic sequence of 15 face-to-face periods was applied to a class of the first year of high school in a public school located in the city of Soledade/RS. The methodological procedures are qualitative in nature and used the following data production instruments: the logbook, initial (diagnostic) and final questionnaires and the materials produced during the didactic intervention. The educational product linked to this dissertation is a didactic sequence, supported by the Three Pedagogical Moments, aimed at high school Chemistry teachers and addresses concepts such as: chemical elements; simple and compound substances; organic and inorganic substances (macro and micronutrients). The initial statements that organic foods have no or little chemistry could be demystified after the application of the didactic sequence when the students understood that: Chemistry is present in everything that exists; organic foods are formed by chemical elements (macro and micronutrients) and bring benefits to health, to the development of plants and to the care of the environment, as they are produced without pesticides; the nutrients present in industrialized fertilizers are the same as those found in organic fertilizers; the production of organic fertilizers is made with food scraps; The organic certification seal guarantees the origin of the food, not its appearance, size and value; organic production can be done in small spaces. It is concluded that the adoption of organic production/food is part of a "lifestyle", which interferes not only in the choice of food and in people's health, but in an entire production chain, in an entire system of environmental and socioeconomic scope. The educational product linked to this dissertation is a free and open-access didactic sequence and is available for download on the website of the Graduate Program in Science and Mathematics Teaching at the University of Passo Fundo, as well as on the EduCapes portal, at the link: http://educapes.capes.gov.br/handle/capes/747846.